Comfort as a factor in stock raising - Cunningham, Claude Carrol (My University, 1903)
Introduction: To be successful in this day and age of specialists attention must be paid to the smallest and most insignificant details of any profession or line of work pursued by man. It is these seemingly little, unimportant things that are the cases of so many failures and small profits. They may be the last straw and if neglected cause disastrous results. The old adage, “Save your pennies and the dollars will care for themselves, “applies to many things other than finances. In the industry of stock-raising this tendency to neglect little matters is perhaps as notorious or more so than in any other line of business. The average farmer supplies the absolutely necessary requirements that are demanded by stock, such as food and a place of confinement, regardless of its quality benefits or condition. The animals likes or dislikes are not taken into consideration, nor is the convenience, comfort, and health of conditions furnished, regarded from the animal’s standpoint. To raise stock with maximum success a farmer must take into consideration all the factors that influence the growth and development of his cattle,. He must sort out and eliminate or modify influences that are unfavorable and encourage and establish those that are favorable. In other words there are ideal conditions under which cattle will grow and develop to the best advantage and the nearer to those ideal conditions the stock are put the more successfully they can be grown. Among other conditions that go to make up the ideal is one that is included under the general term, comfort, and the object of the following production is to discuss and emphasize the influence of the different factors in the environment of cattle that have to do with the comfort and contentment of the animal.
Citation: Cunningham, Claude Carrol. Comfort as a factor in stock raising. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Ideal Conditions Under Which Cattle Thrive Best; Cattle Shelter Influence; Confinement; Theses